Genome-wide association study identifies 8p21.3 associated with persistent hepatitis B virus infection among Chinese - Yuanfeng Li (Nature Portfolio, 2016)
This genome-wide association study on persistent hepatitis B virus (HBV) infection among Chinese confirms previously associated genetic loci while discovering a novel protective locus at 8p21.3. The study also demonstrates the nearby gene INST10 suppresses HBV replication in vitro.